RELATIONSHIP KNOWLEDGE, ATTITUDE, AND PERCEPTION OF BENEFITS WITH DECISION OF THE PREGNANT WOMAN IN VCT IN THE PUSKESMAS AREAS OF MRANGGEN I DEMAK - Aisyah Lahdji; Baratarini Baratarini (Universitas Muhammadiyah Semarang, 2018)
Human Immunodeficiency Virus - Acquired Immuno Deficiency Syndrome (HIV-AIDS) is a contagious disease problem that until now the number of patients is increasing. VCT strategy is at the core of all HIV / AIDS prevention and prevention efforts in the world. Several studieshave confirmed that the utilization of antenatal VCT by pregnant women is still low. The purpose of this study is to analyze the relationship of knowledge, attitudes and perceptions of the benefits of pregnant women in conducting VCT in the Area Puskesmas Mranggen 1 Demak. This research includes analytic observational research with cross sectional approach.The population in this study were all pregnant women in the area of Puskesmas Mranggen I Demak in 2017 conducted in November 2017 until February 2018. The sampling technique used in this study using consecutive sampling. The analysis used was univariate and bivariateusing chi square test using SPSS 16 program. The result of bivariate analysis showed that there was no correlation between knowledge, attitude and perception of benefit with decision of pregnant woman doing VCT with each p value was 0,629 and 0,428 (p > 0.05). The conclusion in this study that there is no significant relationship between knowledge, attitudes and perceptions of benefits to pregnant women's decision to do VCT. Keyword : VCT, Pregnant Women, HIV